2020
DOI: 10.1111/cei.13537
|View full text |Cite
|
Sign up to set email alerts
|

CD40L-stimulated B cells forex-vivoexpansion of polyspecific non-human primate regulatory T cells for translational studies

Abstract: We developed an approach for the expansion of Mauritian cynomolgus macaque polyspecific regulatory T cells (Tregs) through the combination of MHC‐mismatched CD40L‐engineered B cells. Expanded Tregs expressed high levels of FoxP3 and Helios, a high percentage of TSDR demethylation, and strong suppression of naïve T cell responses in vitro. This approach has the potential to be translated to clinical studies for deceased‐donor transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Importantly, these Tregs also expanded after cryopreservation, an important benefit allowing protocol flexibility. Specificity assays confirmed they were suppressive following activation by any APCs whose MHC expression was shared by the CD40L−sBc used during their expansion, proving that they were polyspecific ( Alonso-Guallart et al, 2021 ). Recently, Ezzelarab et al (2020) also used CD40L−sBc of donor origin to expand cynomolgus darTregs that were adoptively-transferred to transplant recipients.…”
Section: Isolation Purification Ex Vivo Expansion and Validation Of Nhp Tregmentioning
confidence: 97%
See 2 more Smart Citations
“…Importantly, these Tregs also expanded after cryopreservation, an important benefit allowing protocol flexibility. Specificity assays confirmed they were suppressive following activation by any APCs whose MHC expression was shared by the CD40L−sBc used during their expansion, proving that they were polyspecific ( Alonso-Guallart et al, 2021 ). Recently, Ezzelarab et al (2020) also used CD40L−sBc of donor origin to expand cynomolgus darTregs that were adoptively-transferred to transplant recipients.…”
Section: Isolation Purification Ex Vivo Expansion and Validation Of Nhp Tregmentioning
confidence: 97%
“…Details of methods developed for isolation and purification of NHP Tregs from blood or tissues, and for expansion and testing of polyclonal, polyspecific or donor Ag-alloreactive (dar) NHP Treg are summarized in Table 1 . Thus, ex vivo expansion of cynomolgus or rhesus Treg after immunomagnetic bead or/and flow sorting has been well-described in response to either polyclonal stimuli ( Gansuvd et al, 2007 ; Anderson et al, 2008 ), allogeneic PBMC ( Porter et al, 2007 ) or dendritic cells (DCs) ( Moreau et al, 2008 ), artificial (a)APCs ( Weiner et al, 2015 ; Zhang et al, 2015 ) or CD40L-stimulated allogeneic B cells (sBc) ( Ezzelarab et al, 2020 ; Alonso-Guallart et al, 2021 ). Most recent attention has focused on expansion of alloreactive Tregs using various protocols.…”
Section: Isolation Purification Ex Vivo Expansion and Validation Of Nhp Tregmentioning
confidence: 99%
See 1 more Smart Citation
“…Alonso-Guallart et al expanded CD40L-sBc derived from MHC-diverse macaques and used them to stimulate and expand Tregs. These expanded Tregs with poly specificities only secreted small amounts of inflammatory cytokines, inhibited naive T cell responses and could be activated by APCs with MHCs shared by the expanded CD40L-sBc (Alonso-Guallart et al, 2021). The new approach shows the potential in clinical applications (Alonso-Guallart et al, 2021).…”
Section: The Effects Of B Cells On Treg In Diseasesmentioning
confidence: 99%
“…The survival of tissue allogeneic transplantation is enhanced in mice which are with ablation of bone marrow, then transplanted with skin allograft and then followed by syngeneic bone marrow transplantation (BMTx) (Gorczynski et al, 2018). Bregs are involved in this process by regulating the capacity of Tregs from donors (Alonso-Guallart et al, 2021). Studies demonstrated that the administration of Bregs in mice with post-BMTx prolonged survival of mice and elevated Treg levels (Gorczynski et al, 2018), and TGF-β aided in this process (Lee et al, 2014).…”
Section: Breg and Its Correlation With Treg In Transplantationmentioning
confidence: 99%